EVALUATION OF THE IMPLEMENTATION OF THE ADMINISTRATIVE INFORMATION SYSTEM OF INDONESIAN MIDWIVES ASSOCIATION IN EAST JAVA - Kasiati Kasiati; Heru Santoso Wahito Nugroho (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2020)
One of the components of the IBI organizational system is an integrated organizational administration system, starting from the central level, provincial level, district / city level, to the lowest level, namely the sub-branch level. Until now, the administrative system has not been well organized, especially in the organizational administration system at the provincial level down to the sub-branch level. One of the obstacles encountered was the inadequate implementation of the Administrative Information System for the Indonesian Midwives Association (SIA-IBI) at the district / city level. It is necessary to evaluate the smooth implementation of SIA-IBI in all districts / cities in East Java Province. The subjects of this descriptive research were all (38) administrators of SIA-IBI. There were 2 variables described in this study, namely: 1) the smooth implementation of SIA-IBI; 2) the obstacles in implementing SIA-IBI. Data on these two variables were collected through direct interviews with all SIA-IBI administrators. The data were analyzed using descriptive statistics, namely frequency and percentage. Based on the data analysis results, it is clear that: 1) all (100%) districts / cities in East Java Province had not been fluent in implementing SIA-IBI; 2) the obstacles faced by SIA-IBI administrators vary widely. The obstacles are grouped into 8 groups, namely: internet connection, double duty, completeness of data, fickle system, limited time, not yet proficient, lack of equipment, and low response to the system. Based on the results, it can be concluded that the implementation of SIA-IBI in all districts / cities in East Java Province has not been going well, and this is related to obstacles from technical and organizational aspects.